Synthesis and characterization of three ternary samarium(III) complexes and their optical properties. Issue 8 (13th September 2020) - Chauhan, Archana; Lohra, Sheetal; Langyan, Ritu
Abstract: Three ternary samarium(III) complexes with 6-methyl-4-oxo-4H-1-benzopyran-3-carboxaldehyde, 4-methyl-1, 10-Phenanthroline, and 2, 2′-Biquinoline and Bathocuproine have been prepared and characterized. The complexes exhibit crystalline character and excellent thermal stability. On irradiation with ultraviolet radiation, the complexes display characteristic emission peaks of samarium(III) ion. The color coordinates, decay curves, and quantum yield have been discussed in detail. The investigations demonstrate that the synthesized complexes might be practically useful in bio-assays, electroluminescent devices, and liquid lasers due to their fascinating optical properties.